From past to present: a bibliometric and visualized study of the most impactful publications on Congenital Diaphragmatic Hernia (CDH) - Shu, Boshen; Riedel, Jan; Gosemann, Jan-Hendrik; Wagner, Richard; Peukert, Nicole; Lacher, Martin; Mayer, Steffi; Aubert, Ophelia (Journal of pediatric surgery, 2025)
Background - Congenital diaphragmatic hernia (CDH) is a severe birth defect characterized by significant infant mortality and morbidity. While numerous articles have been published on CDH, little is known about the characteristics of the most impactful articles. In this study, we aimed to identify and characterize the most important publications in the CDH field from a bibliometric perspective. - Methods - Articles addressing CDH were retrieved in October 2024 from the Web of Science™ and ranked by citation number. The top 100 publications were analyzed for their bibliometric parameters including number of citations, subject of study, level of evidence, country of origin, journals and publication year. A visualized study of identified articles was performed using the VOSviewer software. - Results - In total, 4637 publications with 84,163 citations from 713 journals were identified. The 100 most cited papers were published between 1962 and 2018, mainly in the Journal of Pediatric Surgery (37 %). The USA was the leading country for number of publication and degree of collaboration with other countries. Citations per article ranged from 117 to 497 (median 162). Retrospective studies (36 %) and studies with low evidence level IV (41 %) dominated. The terms CDH, extracorporeal membrane oxygenation (ECMO), survival, pulmonary hypoplasia, preoperative stabilization, prenatal diagnosis, high frequency oscillatory ventilation (HFOV) and fetoscopic endoluminal tracheal occlusion (FETO) were identified as high-frequency keywords in co-occurrence analysis. Morbidity and mortality (21 %), surgical management (16 %) and animal model research (14 %) were the top three topics of interest. - Conclusions - Our findings identify the most referenced works, including the countries and journals of origin, in CDH over the past five decades. These manuscripts highlight advances in the understanding and management, with an increased focus on prenatal diagnosis, long-term outcomes and innovative treatments. However, the field remains hindered by a lack of high-level evidence studies, underscoring the need for more randomized controlled trials and translational research to improve clinical outcomes. - Level of Evidence - IV. - Type of Study - Original Research.
Online verfügbar: 7. Juni 2025, Artikelversion: 17. Juni 2025
Gesehen am 18.08.2025